الأدوات الروابط في الجمل التي لها محل من الأعراب دراسة نصية في سورة البقرة - حنكة, مسعودي, باهية أسماء (University of El-oued, 2021)
يهدف هذا البحث للكشف عن قيمة وأهميّة الروابط في القرآن الكريم و بالأخص في سورة البقرة وما تتركه من أثر في نفس السامع فمن خلال الدراسة يتبيّن لنا البعد النصّي لأدوات الربط في النص القرآني. لقد اعتمدت هذه الدراسة على المنهج الوصفي التحليلي الذى يمكن من خلاله احصاء الجمل التي لها محل من الإعراب في سورة البقرة واستخراج مختلف الروابط منها. وقد توصل هذا البحث إلي أنّ الأدوات الروابط مختلفة ومتعددة في هذه السورة منها الاحالة , التكرار , الحذف و حروف العطف وغيرها.كل هذه الأدوات ساهمت في اتساق وانسجام النص القرآني وتماسكه. وفي هذا البحث حاولنا الكشف عن الدور الترابطي الذى تؤديه أدوات الربط في سورة البقرة , بما يحتويه هذا الدور من أهمية بالغة تتمثل في سبك الكلام سبكاً سليما وصياغته صياغة محكمة. حيث تعد ظاهرة الربط من أهم الظواهر اللغويةّ, التي تسهم بشكل أو بآخر في بناء النظام اللغوي وتماسك تراكيبه والتحام أجزاءه .This research aims to reveal the value and importance of links in the Noble Qur’an, especially in Surat Al-Baqarah, and its impact on the listener. This study relied on the analytical descriptive approach, through which it is possible to count the sentences that have a place of parsing in Surat Al-Baqarah and extract the various links from them. This research has concluded that the linking tools are different and multiple in this surah, including assignment, repetition, omission, conjunctions and others. All these tools contributed to the consistency and coherence of the Qur’anic text. In this research, we tried to reveal the associative role played by the linking tools in Surat Al-Baqarah, as this role contains of great importance represented in casting words in a sound manner and formulating them in a tight formulation. Where the phenomenon of linkage is one of the most important linguistic phenomena, which contribute in one way or another to the construction of the linguistic system and the coherence of its structures and the fusion of its part
Keywords: الربط-الادوات –الجمل- الاعراب; conjunctions - tools - sentences - syntax